Conformism and Public News - Rochon, Celine (IMF Working Papers; Working Paper ;, 2011)
We study a model where investment decisions are based on investors' information about the unknown and endogenous return of the investment. The information of investors consists of endogenously determined messages sold by financial analysts who have access to both public and private information on the return of the investment. We assume that the return of the investment is correlated with the aggregate investment. This results into a beauty contest among analysts (or a "conformism" effect). In equilibrium, analysts sell all the information they have to all the investors. A striking result is that there are sometimes multiple equilibria. There are equilibria where the beauty contest is exacerbated. Because of the correlation across analysts' information sources, not all the information available in the economy is transmitted to investors.